2020
DOI: 10.19173/irrodl.v20i5.4545
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Devolved Model of Management of OER? The Case of the Irish Higher Education Sector

Abstract: This paper reports on the research findings from a national project examining the issues in creating, sharing, using, and reusing open educational resources (OER) in the context of the development of open education in Ireland. One important aspect of the research was to investigate the potential for using existing institutional research repository infrastructure for the purpose of ingesting, managing, and discovering OER produced by academics. This approach would imply a move from previous strategy around a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Some of the earliest efforts were preserving OER in institutional or educational repositories (Risquez et al, 2020;Santos-Hermosa et al, 2020). Also, certain library competencies, such as knowledge in copyright, licencing and intellectual property, have allowed them to participate in the creation of OS policies (Atenas et al, 2020;Santos-Hermosa et al, 2020) and contribute to institutional governance (Walz, 2017).…”
Section: Literature Review Library Support For Oermentioning
confidence: 99%
“…Some of the earliest efforts were preserving OER in institutional or educational repositories (Risquez et al, 2020;Santos-Hermosa et al, 2020). Also, certain library competencies, such as knowledge in copyright, licencing and intellectual property, have allowed them to participate in the creation of OS policies (Atenas et al, 2020;Santos-Hermosa et al, 2020) and contribute to institutional governance (Walz, 2017).…”
Section: Literature Review Library Support For Oermentioning
confidence: 99%
“…Finally, the sustainability of OER and their infrastructures is a clear challenge to the continuity of initiatives (Orr et al 2015)as shown by some of the national, regional, and institutional cases discussed hereand there is not a single business model that may work in every context. For example, the decision to not continue the UKOER program (2009)(2010)(2011)(2012) and the subsequent retirement of the UK OER national repository (Jorum) implied a shift from funding and responsibility at national level to individual institutions, favoring a devolved model where institutions have to find their own resources and meant optimizing resources by, for instance, including OER collections into open-access research repositories (Risquez et al 2020).…”
Section: Challenges and Future Researchmentioning
confidence: 99%
“…There is an essential heterogeneity of open education practices. They have mainly focused on the production, use, and mobilization of various open educational resources [5]- [7], the analysis of the support infrastructure for teaching [8] and the organization and implementation of learning ecosystems [9]. Other practices include the performances of techniques for open learning spaces [10], innovative methodologies such as gamification [11], and Education 4.0 tools to support sustainable open education [12], [13].…”
Section: Introductionmentioning
confidence: 99%